ANALISIS PERMINTAAN SIMPANAN WADI’AH YAD AD DHAMANAH DI BANK SYARIAH MANDIRI DI KOTA PEKANBARU - Fahmi Reza Fikri; Mayes Anthoni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The purpose of this study is to determine the profit sharing system, savings interest rates, location or number of Islamic bank outlets, and the level of income determine the demand to open deposits yad ad dhamanah at Bank Syariah Mandiri in Pekanbaru City. This study uses the theory of Kasri and Kassim (2009) which explains that the factors affecting demand for savings in Indonesia are 1) the level of profit sharing, 2) the number of Islamic bank outlets and 3) the level of income. The data collection method uses the survey method by using secondary data obtained from the questionnaire. Researchers determined the sample in this study is 100 Bank Syariah Mandiri customers in the city of Pekanbaru. The variables used are profit sharing system, location, income level, and demand. Revenue sharing system known to an average of 3.88 respondents' answers are in the criteria agreed. Location variables are known to an average of 3.75 respondents' answers are in the agreed criteria. Variable income level is known to an average of 3.85 respondents' answers which are in the agreed criteria. The results showed that the revenue sharing system, location and level of income affect the demand for deposits. The request to open a yad ad dhamanah wadi'ah deposit at Bank Syariah Mandiri in Pekanbaru city because the revenue sharing aspect is one of the highest aspects.Keywords: Profit sharing system, savings interest rates, location or number of Islamic bank outlets, income level, demand.